2016
DOI: 10.5114/wo.2016.60074
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression and cognitive coping strategies and health locus of control in patients with ovary and uterus cancer during anticancer therapy

Abstract: Aim of the studyThe crisis associated with cancer may contribute to the development of anxiety and depressive disorders. Contemporary psycho-oncology focuses on the psychological determinants of the cancer patients functioning to find which disease-coping strategies help the healing process, facilitate the establishment of a good therapeutic relationship and the process of adapting to difficult situations. Aim of the study was assess the psychological functioning of patients with cancer of reproductive organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 14 publications
4
31
0
1
Order By: Relevance
“…Using the cutoff 8+, the percentages of elevated anxiety and depression in the total sample are 21 and 23%, respectively [ 36 ]. In the case of Polish oncological patients, it was documented that in population with gynaecological and breast cancers, the average anxiety was ranging from 7.0 to 8.2, and average depression from 6.1 to 8.4 depending on disease stage and therapeutic method [ 37 , 38 ]. In Polish patients with gastrointestinal tract cancers, it was found that the average severity of anxiety was 6.7 and average severity of depression was 4.8 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the cutoff 8+, the percentages of elevated anxiety and depression in the total sample are 21 and 23%, respectively [ 36 ]. In the case of Polish oncological patients, it was documented that in population with gynaecological and breast cancers, the average anxiety was ranging from 7.0 to 8.2, and average depression from 6.1 to 8.4 depending on disease stage and therapeutic method [ 37 , 38 ]. In Polish patients with gastrointestinal tract cancers, it was found that the average severity of anxiety was 6.7 and average severity of depression was 4.8 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance consists of accepting that the event has occurred as well as emotional acceptance, which is a willingness to feel one’s positive and negative emotions without trying to control, change, or reject these feelings. Acceptance of the event - in this case, the cancer diagnosis - has been consistently associated with less distress among cancer patients [11, 27, 28], including among women diagnosed with gynecological cancer [29]. Although less studied, emotional acceptance has been associated with less distress among cancer patients [27, 30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, although helplessness coping and anxious preoccupation predict decreased health-related quality of life, religious coping, optimistic coping, and problem focused coping positively predict increased health-related quality of life among women living with breast cancer. [22][23][24] Similarly, having a fighting spirit which involves individual's determination to significantly deal with their illness has been found to be positively associated with health-related quality of life among the patients, while fatalism predicts decreased health-related quality of life among the patients. 25 These findings point to the fact that maladaptive coping is detrimental to the health and wellbeing of cancer patients.…”
Section: Introductionmentioning
confidence: 99%